Linkage detection between climate oscillations and water and sediment discharge of 10 rivers in Eastern China - Zhang, Feng; Zhang, Li; Zhong, Yaozhao; Zou, Huangjie; Lai, Xiaohe; Xie, Yanshuang (Frontiers in Marine Science, 2024)
Water discharge and sediment load are often controlled by a combination of factors. However, the relationship between water and sediment load changes and meteorological oscillations has rarely been explored for different river sizes. Explanations for the various responses of water-sediment changes to meteorological factors in different rivers is important for understanding global hydrology. In this study, we analyzed data from 2002-2022 using cross-wavelet and wavelet coherence in an attempt to characterize the effects of large-scale climatic oscillations on 10 rivers in eastern China. Comparing the results shows that water releases lag three months or more behind SST variations. It also oscillates interannually (mostly every 8-16 months). Most rivers runoff lags changes in PDO by three months or more. The impact of ENSO (El Niño-Southern Oscillation) on each river basin gradually decreases from south to north. The impacts on northern rivers such as the Yellow River, Huai Riverand Liao River are weaker. At the same time, the water discharge changes in the Pearl River and Minjiang River basins in southeastern China are extremely rapid and sensitive to ENSO events. Meanwhile, the impacts of ENSO on large rivers lasted throughout the study period, while the impacts of ENSO on smaller rivers had intermittent periods, and the response rates of geographically similar mountain and stream-type rivers were not the same. The effect of the PDO (Pacific Decadal Oscillation) warm and cold phases was different for each region. Our research contributes to understanding the relationship between rivers and climate oscillations, advancing Water-Sediment Balance and Global Sustainability—key goals of the United Nations 2030 Agenda for Sustainable Development.